¿Y si no ejercen su derecho de adquisición preferente, podemos vender? La importancia de reglas claras para el ejercicio de este derecho - Álvarez-Calderón, Diego Carrión (2020)
The following article addresses the topic of Right of First Refusal, the reasons for its existence and regulation, also it will analyze theregulations adopted in the Peruvian legal system, the civil perspective of the exercise of this right, finally concluding with the challengesfaced in reality. The author will propose recommendations onto many of the outlined issues, albeit there not being a simple solution and, each challenge should be analyzed on a case-by-case basis as the best way to reduce or eliminate said problems.